Tissue Specific Origin, Development, and Pathological Perspectives of Pericytes - Yamazaki, Tomoko; Mukouyama, Yoh-suke (Frontiers in Cardiovascular Medicine, 2018)
Pericytes are mural cells surrounding blood vessels, adjacent to endothelial cells. Pericytes play critical roles in maturation and maintenance of vascular branching morphogenesis. In the central nervous system (CNS), pericytes are necessary for the formation and regulation of the blood-brain barrier (BBB) and pericyte deficiency accompanies CNS diseases including multiple sclerosis, diabetic retinopathy, neonatal intraventricular hemorrhage, and neurodegenerative disorders. Despite the importance of pericytes, their developmental origins and phenotypic diversity remain incompletely understood. Pericytes express multiple markers and the origin of pericytes differs by tissue, which may cause difficulty for the identification and understanding of the ontogeny of pericytes. Also, pericytes have the potential to give rise to different tissues in vitro but this is not clear in vivo. These studies indicate that pericytes are heterogeneous in a tissue- and context- dependent manner. This short review focuses on recent studies about identification of pericytes, heterogeneous origin of pericytes during development and in adults, and the differentiation capacity of pericytes, and pericytes in pathological settings.